Stroke Findings in the Women's Health Initiative - Wassertheil-Smoller, Sylvia; Kaplan, Robert C.; Salazar, Christian R. (Seminars in Reproductive Medicine, 2014)
The Women's Health Initiative (WHI) clinical trials of estrogen with or without progestin versus placebo in 27,341 postmenopausal women are the largest randomized, placebo-controlled, double-blind clinical trials to look at the effect of hormone therapy on the outcomes of stroke, dementia, and cognition. Data from a parallel prospective observational study of 93,676 women examine biomarkers and risk factors associated with stroke. We summarize the results of 29 published articles in the WHI with stroke or cognition as outcomes of interest. Estrogen alone or in combination with progestin resulted in approximately 50% excess risk of ischemic stroke and in a 76% excess risk of dementia in women 65 years or older. Other risk factors for stroke identified in the WHI were panic attacks, depression, use of antidepressants (particularly selective serotonin reuptake inhibitors for hemorrhagic but not ischemic stroke), high triglycerides, low walking speed, long sleep duration, certain inflammatory factors, and systolic blood pressure variability. Hormone therapy has adverse effects on the brain as manifested by higher risks of stroke and dementia. Additional risk factors for stroke identified in WHI should be followed up to determine if reversing them would result in lower stroke rates.
Keywords: stroke; hormone therapy; Women's Health Initiative; WHI; dementia; postmenopausal women